2022
DOI: 10.3390/ijerph192214829
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of School Leaders’ Attitudes and Health Literacy to the Implementation of a Health-Promoting Schools Approach

Abstract: Schools are considered as important settings for health education and the promotion of functioning, healthy people. Health-promoting schools (HPS) take a holistic approach to health promotion that addresses all school levels and members of the school community. Although it is assumed that school leaders are crucial in the implementation of HPS, little is known so far about which specific factors are relevant. The purpose of this study was to analyze the role of school leaders’ attitudes, health literacy, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
0
7
1
2
Order By: Relevance
“…The majority of senior leaders in this study reported low well-being, lower than the general adult population pre-pandemic [ 60 ] and COVID-HL international study data from Hong Kong [ 33 , 34 ] and Switzerland [ 35 ]. Elsewhere, reports from 2020 to 2022 suggest negative impacts of the sustained work-related pressures on senior leaders’ well-being and mental health [ 20 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of senior leaders in this study reported low well-being, lower than the general adult population pre-pandemic [ 60 ] and COVID-HL international study data from Hong Kong [ 33 , 34 ] and Switzerland [ 35 ]. Elsewhere, reports from 2020 to 2022 suggest negative impacts of the sustained work-related pressures on senior leaders’ well-being and mental health [ 20 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HL for “understanding” (aOR = 2.2, 95% CI 1.7; 3.0) and “applying” (aOR = 2.2, 95% CI 1.7; 3.0) was significantly associated with HPS-principles. As Betschart et al [ 48 ] indicated, attitudes toward health promotion amplified the positive relationship between HL and HPS approach. Specifically, when positive attitudes and understanding toward health promotion occurs, school principals’ HL is significantly associated with HPS.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, HSCs sometimes indicated a lack of a sense of authority to act on their changing role, for example in asking people to actively join the HPS team. This highlights the need to invest in the commitment of formal school leaders for the successful implementation of the HPS framework ( Betschart et al ., 2022 ).…”
Section: Discussionmentioning
confidence: 99%